Evidence-Based Medicine: Cutaneous Facial Malignancies. Issue 1 (January 2017) - Connolly, Karen L.; Nehal, Kishwer S.; Disa, Joseph J.
Abstract : Learning Objectives: After studying this article, the participant should be able to: 1. Identify clinical features of nonmelanoma skin cancer; 2. Distinguish low-risk versus high-risk basal cell carcinoma and squamous cell carcinoma; 3. Define appropriate management based on current guidelines for various types of basal cell and squamous cell carcinoma. Summary: Skin malignancies are the most prevalent cancers, and plastic surgeons are often the primary physicians engaged in diagnosis and management of these lesions. Proper management includes distinguishing between high-risk and low-risk lesions and determining treatment accordingly. The aim of this Continuing Medical Education article is to review the diagnosis and management of common and uncommon facial skin malignancies, including basal cell carcinoma, squamous cell carcinoma, actinic keratosis, keratoacanthoma, Merkel cell carcinoma, atypical fibroxanthoma, sebaceous carcinoma, and microcystic adnexal carcinoma. Abstract : Supplemental Digital Content is available in the text.